2015
DOI: 10.2139/ssrn.2577569
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Policy-Mixes of Research and Innovation Policies in Central and Eastern European Countries

Abstract: Observing the CEE members of the EU (EU10 countries) from a distance, they certainly used to share major structural similarities given their historical legacies, as well as certain 'unifying' effects of their transition to market economy and democracy. Yet, a closer look reveals important elements of diversity in (a) the structure of their national innovation system, (b) the direction of recent structural changes, (c) innovation performance, and (d) patterns of business-academia collaboration. Given this diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 80 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…URL: https://www.afd.fr/en/development-aid-whats-it-all-about (accessed on 21.03.2020). 25 AFD (2015), Agence Française de Développement. URL: https://issuu.com/objectif-developpement/docs/csr_gri_ report_2015_afd_group (accessed on 21.03.2020).…”
Section: The German Development Bank (Kfw)mentioning
confidence: 99%
See 1 more Smart Citation
“…URL: https://www.afd.fr/en/development-aid-whats-it-all-about (accessed on 21.03.2020). 25 AFD (2015), Agence Française de Développement. URL: https://issuu.com/objectif-developpement/docs/csr_gri_ report_2015_afd_group (accessed on 21.03.2020).…”
Section: The German Development Bank (Kfw)mentioning
confidence: 99%
“…stages of economic (and thus financial) transition [21][22][23][24][25][26][27][28][29][30] in countries that decades ago still were part of a much more secluded economic sphere [31][32][33][34][35][36][37][38][39][40], and thus had thrived less, economically and financially, despite their mostly healthy base of human capital. One of the most recent and most comprehensive reports is by UNECE [41]; thus, providing a cutting-edge and neutral set of assessments and recommendations for countries with a similar structure as Russia.…”
mentioning
confidence: 99%
“…Since this is the primary monitoring tool of the EC which is reflective of the EU's innovation policy approach and influencing it at the same time, it is essential to thoroughly analyse it. In a recent research paper, Havas et al (2015) revealed a strong bias towards R&D-based innovations, that is, towards the narrow approach of innovation policies. As they argue, among the 25 indicators: '10 indicators are only relevant for, and a further four mainly capture, R&Dbased innovations; seven could be relevant for both types of innovations; and a mere four focus on non-R&D-based innovations.…”
Section: Europe 2020: Significant Changes In European Innovation Policymentioning
confidence: 99%
“…However, it has also been highlighted that R&D and innovation policies will be a factor of further divergence across the EU, since they reinforce existing agglomerations and growth poles (Gorzelak, 2015). Furthermore, it has been postulated that innovation policies need to reflect country and region specific conditions in CEECs rather than 'best practice' from advanced EU15 countries (Havas et al 2015). This has also implication for the role of FDI in the catch-up process.…”
Section: Policy Implications For Europe and Ceecsmentioning
confidence: 99%